2023
DOI: 10.1136/bmjopen-2022-068916
|View full text |Cite
|
Sign up to set email alerts
|

Mediating role of psychological distress and domestic violence in the association of fear of COVID-19 with marital satisfaction and sexual quality of life among women of reproductive age: An Iranian cross-sectional study

Abstract: ObjectivesThis study aimed to determine the mediating role of psychological distress and domestic violence in the association of fear of COVID-19 with marital satisfaction and sexual quality of life (QoL) among Iranian women of reproductive age.MethodsA cross-sectional study comprising 324 married women was conducted. Online convenience sampling was used to collect data. SPSS PROCESS macro was used for the mediation analysis. The direct and indirect effects of the fear of COVID-19 on sexual QoL and marital sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Nik-Azin et al also reported a weak but significant association between female sexual functioning with the general quality of life and its psychological and environmental sub-dimensions [51]. Other studies have shown that having a good sexual quality of life is associated with quality of life more generally which is likely to be associated with lower levels of depression [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Nik-Azin et al also reported a weak but significant association between female sexual functioning with the general quality of life and its psychological and environmental sub-dimensions [51]. Other studies have shown that having a good sexual quality of life is associated with quality of life more generally which is likely to be associated with lower levels of depression [54,55].…”
Section: Discussionmentioning
confidence: 99%